PERANCANGAN DAN IMPLEMENTSI ALAT UKUR DAYA LISTRIK ARUS BOLAK-BALIK SATU FASA BERBASIS PERSONAL COMPUTER - Naga, Dali S.; Thomas, Thomas; Arto, Rudy (Universitas Tarumanagara, 2006)
Design measurement instrument is not easy. Because that instrument to measure something, it is mean that used as reference, so in designing the used reference is as good as possible. Measuring electric power can be done in many ways, measure voltage, current, and power factor then cross that is the one way. This electric power equipment for measure electronic equipment and electrics equipment. Analog to Digital Converter (ADC) determines the capability of this Digital Measurement Instrument. ADC0804LCN is product of National Semiconductor, one of ADC can be used. ADC0804LCN is 8bit resolution ADC with serial control. Maximum clock is 640 KHz determining data transfer rate. Microcontroller is used to control ADC0804LCN.